ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA RSUD SUNGAI RUMBAI - Nur Izati Fitriani; Sri Adella Fitri; Khairul Marlin; Yeni Melia (IAIN BATUSANGKAR, 2022)
The accounting information system is one of the important things that needs to be considered in managing the implementation of a good organization, including in government organizations. The Sungai Rumbai Regional General Hospital is a new hospital that was established in 2017 and was inaugurated as a hospital on the basis of the Regional Public Service Agency (BLUD) in 2019, thus the RSUD has flexibility in making hospital cash disbursements that are adjusted to income hospital with basic BLUD. The purpose of this study is to determine and analyze the accounting information system for cash receipts and disbursements at Sungai Rumbai Hospital is good or not. The type of research carried out is descriptive qualitative with data collection techniques that the author uses, namely interviews, observations, and documentation. The analysis technique used is data reduction, data presentation, and drawing conclusions. In the results of the implementation of this study in the form of an analysis of the state of the accounting information system for cash receipts and disbursements at Sungai Rumbai Hospital with accounting information system theory that is generally accepted in several books and references. The results of the research on the Accounting Information System for Cash Receipts and Expenditures at Sungai Rumbai Hospital have used the SIMRS application, but are still carried out in stages. For now, SIMRS has only been implemented in the staffing and patient registration section. Meanwhile, the receipt and expenditure accounting information system is still done manually. The Accounting Information System for Cash Receipts and Expenditures at Sungai Rumbai Hospital has fulfilled several elements such as Human Resources, procedures, forms, and tools used are appropriate. However, the notes and reports are still not in accordance with the literature theory.Keywords: Accounting Information Systems; Cash Receipts; Cash Expenditures ABSTRAKSistem informasi akuntansi menjadi salah satu hal penting yang perlu diperhatikan dalam mengelola terselenggaranya organisasi yang baik, termasuk dalam organisasi pemerintahan. Rumah Sakit Umum Daerah Sungai Rumbai merupakan rumah sakit milik pemerintahan yang baru diresmikan pada tahun 2017 dan telah diresmikan sebagai Rumah sakit dengan basis Badan Layanan Umum Daerah (BLUD) pada akhir tahun 2019, dengan demikian RSUD memiliki fleksibilitas dalam melakukan pengeluaran kas rumah sakit yang disesuaikan dengan pendapatan BLUD Rumah Sakit. Tujuan penelitian ini yaitu untuk mengetahui dan menganalisis sistem informasi akuntansi penerimaan dan pengeluaran kas pada RSUD Sungai Rumbai sudah baik atau belum. Jenis penelitian yang dilakukan yaitu kualitatif deskriptif dengan teknik pengumpulan data yang penulis gunakan yaitu wawancara, observasi, dan dokumentasi. Teknik analisis yang digunakan yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Dalam hasil implementasi penelitian ini berupa analisis keadaan sistem informasi akuntansi penerimaan dan pengeluaran kas RSUD Sungai Rumbai dengan teori sistem informasi akuntansi yang berlaku umum di beberapa buku dan referensi. Hasil penelitian Sistem Informasi Akuntansi Penerimaan dan Pengeluaran kas di RSUD Sungai Rumbai telah menggunakan aplikasi SIMRS, namun masih dilakukan secara bertahap-tahap. Untuk saat ini SIMRS baru diberlakukan di bagian kepegawaian dan pendaftaran pasien. Sedangkan sistem informasi akuntansi penerimaan dan pengeluaran masih dilakukan secara manual. Sistem Informasi Akuntansi Penerimaan dan Pengeluaran kas di RSUD Sungai Rumbai telah memenuhi beberapa unsur seperti Sumber Daya Manusia, prosedur, formulir, dan alat yang digunakan sudah sesuai. Namun pada catatan dan laporan masih belum sesuai dengan teori kepustakaan. Kata Kunci: Sistem Informasi Akuntansi; Penerimaan kas; Pengeluaran kas